Differences between selected volatile aromatic compound concentrations in sludge samples in various steps of wastewater treatment plant operations. (1st November 2019) - Byliński, Hubert; Aszyk, Justyna; Kubica, Paweł; Szopińska, Małgorzata; Fudala-Książek, Sylwia; Namieśnik, Jacek
Abstract: Sewage sludge, one of the main wastes generated during wastewater treatment, constitutes an important source of emissions of volatile chemical compounds such as volatile aromatic compounds These substances may undergo various changes as a result of operations and unit processes, which affects their concentrations in sewage sludge. An important factor determining the potential hazardousness of volatile organic compounds is the quality of wastewater delivered to wastewater treatment plants and the technical and equipment solutions applied to wastewater. In this study, a rapid and sensitive headspace gas chromatography method, coupled with tandem mass spectrometry using the standard addition method, was developed for the determination of selected volatile aromatic compounds in sewage sludge samples collected at different stages from three wastewater treatment plants located in Poland. This study attempted to assess the relationship between differences in the emissions of representative VACs and the given stage of the technological process within three analysed wastewater treatment plants. Toluene was detected with the highest frequency in analysed samples, at concentrations varying from 0.234 ± 0.035 ng/g of sludge to 28.3*10 2 ±3.2*10 2  ng/g of sludge. The highest concentration levels were determined for p-cresol, with concentrations ranging from 44.0*10 1 ±5.6*10 1  ng/g of sludge (sludge from aerobic chamber, wastewater treatment plant no.2) to 47.7*10 2 ±6.9*10 2  ng/g of sludge (sludge from aerobic chamber, wastewater treatment plant no.1), while the lowest concentration levels were observed for chlorobenzene, with concentrations ranging from 0.1300 ± 0.0030 ng/g of sludge (sludge from anaerobic chamber, wastewater treatment plant no.2), to 0.2606 ± 0.0046 ng/g of sludge (primary sludge, wastewater treatment plant no.1). The repeatability of the method was better than 10%, with accuracy levels in the ranges 89%–108%.Wastewater treatment technologies and residual sludge management in the selected wastewater treatment plantsinfluenced volatile aromatic compounds emission. Furthermore, the diversity of the wastewater quality, depending on the catchment area, is also an important factor determining the differentiation in volatile aromatic compounds emission. The microbial composition of raw wastewater highly influenced not only the treatment effectiveness of wastewater treatment plants but also the production of intermediate products, such as volatile aromatic compounds, which may contribute to odour emissions. Graphical abstract: Image 1 Highlights: Sensitive determination of selected volatile aromatic compounds in sludge samples. Concentration of toluene, p-cresol and skatole related with type of sewage sludge. The microbial composition highly influenced the production of p-cresol and skatole.